2000
DOI: 10.1016/s0896-6273(00)81145-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Homer EVH1 Domain-Peptide Complex Reveals a New Twist in Polyproline Recognition

Abstract: Homer EVH1 (Ena/VASP Homology 1) domains interact with proline-rich motifs in the cytoplasmic regions of group 1 metabotropic glutamate receptors (mGluRs), inositol-1,4,5-trisphosphate receptors (IP3Rs), and Shank proteins. We have determined the crystal structure of the Homer EVH1 domain complexed with a peptide from mGluR (TPPSPF). In contrast to other EVH1 domains, the bound mGluR ligand assumes an unusual conformation in which the side chains of the Ser-Pro tandem are oriented away from the Homer surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
1
5

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 71 publications
6
173
1
5
Order By: Relevance
“…With the exception of the recently characterized Homer1g [111], exons 2-5 encode an Enabled/ vasodilator-stimulated phosphoprotein (Vasp) homology 1 (EVH1) domain [119,120], which is similar in sequence to other Ena/Vasp proteins that regulate cytoskeleton dynamics [121].…”
Section: Molecular Aspects Of Homer Proteinsmentioning
confidence: 99%
“…With the exception of the recently characterized Homer1g [111], exons 2-5 encode an Enabled/ vasodilator-stimulated phosphoprotein (Vasp) homology 1 (EVH1) domain [119,120], which is similar in sequence to other Ena/Vasp proteins that regulate cytoskeleton dynamics [121].…”
Section: Molecular Aspects Of Homer Proteinsmentioning
confidence: 99%
“…Mutation and structural analysis revealed that the EVH1 domain binds the sequence PPXXF [12][13][14]. Subsequent work indicated that the EVH1 domain can also bind the sequence øPPXF and the novel ligand LPSSP [15].…”
Section: Homers Localization and Binding To Ca 2+ Signaling Proteinsmentioning
confidence: 99%
“…The effect of Homer1 in neuronal mGluRs Ca 2+ signaling appears to be neuron-type specific. Homer1 binds to the proline-rich motifs PPXXF in the C terminus of mGluRs [12] and the N-terminus of the IP 3 Rs [15], linking them to the Shank family proteins in the PSD to form a Ca 2+ signaling complex [9,29]. Homer1 and Shank target the mGluRs to the plasma membrane when co-expressed in HeLa and other cell types [6,8,9,11,16,17,26].…”
Section: Homer1 In Neuronal Ca 2+ Signalingmentioning
confidence: 99%
“…These genes encode 47-48 kDa proteins that feature an N-terminal Enabled/Vasp homology (EVH1) (Gertler et al, 1996;Beneken et al, 2000) domain of the Ena/VASP protein family (Ponting and Phillips, 1997) and a C-terminal coiled-coil domain and leucine zipper (Kato et al, 1998;Sun et al, 1998;Xiao et al, 1998;Tadokoro et al, 1999) for oligomerization. The EVH1 domain binds a proline-rich motif (PPXXFR) Beneken et al, 2000) in key components of synaptic signal transduction pathways for calciuminduced and transmitter-induced calcium release (C/TICR). This motif resides in the metabotropic glutamate receptors mGluR1a and mGluR5a/b, in ryanodine receptors (RyRs), in inositol triphosphate [Ins(1,4,5)P3] receptors , and in Shank proteins that are part of the NMDA receptor-associated PSD-95 complex .…”
Section: Abstract: Immediate Early Gene; Induced Neuronal Activity; mentioning
confidence: 99%
“…Exon 1 harbors the 5Ј-untranslated region and contains the translational initiation codon ATG at its 3Ј end. The EVH1 domain, characteristic of all Homor proteins (Beneken et al, 2000), is encoded by exons 2-5, whereas the coiled-coil and leucine zipper domains of the long Homor 1 forms are encoded by exons 6 -10. Exon 10 features 186 nucleotides of translated sequence followed by ϳ2.7 kb of 3Ј UTR.…”
Section: Homer 1 Gene Organizationmentioning
confidence: 99%